Causal association between thyroid function and the risk of infertility: a Mendelian randomization study - Liu, Qinyu; Qiu, Yingkun; Jiang, Jialin; Long, Shushu; Zhu, Chengyu; Chen, Gang; Wen, Junping (Frontiers in Endocrinology, 2024)
Objectives: Thyroid dysfunction is commonly associated with the risk of infertility in both females and males. However, recent randomized controlled trials have demonstrated that thyroid function levels in females are not significantly related to infertility, and evidence on the association between male thyroid function and infertility is limited. We aim to investigate the association between thyroid function levels and infertility in both females and males. Method: A two-sample Mendelian randomization study was conducted using four methods, with the inverse variance weighted method (IVW) as the primary approach. Data on thyroid function as the exposure were obtained from the ThyroidOmics Consortium and UK Biobank, including over 700,000 individuals from a large meta-analysis of genome-wide association studies for thyroid function and dysfunction. The outcome data for infertility in both sex encompassed more than 70,000 individuals from the FinnGen Consortium. All participants were adults of European ancestry. The MR Egger regression intercept and Cochran's Q test were employed to evaluate directional pleiotropy and heterogeneity. Results: The results indicated no causal effect of thyroid-stimulating hormone (TSH) and free tetraiodothyronine (fT4) on female and male infertility. Furthermore, no causal association between hypo- and hyperthyroidism and infertility were identified. Notably, we observed a causal relationship between high TSH and endometriosis-related infertility (OR=0.82, 95% CI: 0.74–0.91, P = 1.49E-04). Conclusions: This study did not find evidence for casual relationship between thyroid function levels and risk of infertility. The findings suggest that overall thyroid function levels may not be a significant predictor of infertility risk.